Fiscal Decentralisation and Economic Development in Selected Unitary European Countries - Irena Szarowská (European Financial and Accounting Journal, 2014)
The article provides direct empirical evidence on fiscal decentralisation and economic development in selected European countries in a period 1995-2012. The research (based on data taken from OECD Fiscal Decentralisation Database and OECD) is performed on a panel, which contains 17 unitary countries. Explanatory variables are not examined in individual regressions, but study newly uses Generalized Method of Moments. For a model specification, Dynamic Panel Data Model Wizard is applied. Results of dynamic panel analysis suggest positive and statistically significant impact of expenditure decentralisation and stronger but negative effect of revenue decentralisation on economic development. Effect of tax decentralisation seems to be negative but statistically insignificant. These findings are enormously interesting as the relationship between the different decentralisation measures and economic performance evolves in opposite directions and countries tend to increase revenue fiscal decentralisation over the last years.
Keywords: E62; H71; H72; H77; 650; Fiscal decentralisation; Economic growth; Dynamic panel data